The Ethnographic Study of Cake Pasung as Local Wisdom in Developing Naturalistic Intelligence Among Generation Alpha - Mufarochah, Siti; Maulaya, Ahmad Husein; Sholikha, Mar’atus; Zulfah, Irma Maulidah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The optimization of multiple intelligences in children can be stimulated through various forms of local wisdom, one of which is the traditional food cake pasung in Drancang village Menganti Gresik. This study focuses on local wisdom in the form of cake pasung as a medium for strengthening the naturalistic intelligence of generation alpha. The objective is analyze how generation alpha develops their naturalistic intelligence through the cultural values embedded in cake pasung. The research employed a qualitative method with an ethnographic approach, involving four categories of informants: generation alpha, parents, community leaders, and educators. Data collection techniques included observation, semi-structured interviews, and documentation study, while data analysis and validation were carried out through source and technical triangulation to ensure credibility and validity. Findings reveal local wisdom of cake pasung fosters generation alpha’s naturalistic intelligence, positioning it not merely as food but as a culturally contextual educational medium rooted in indigenous traditions.